(untitled) (Research, Society and Development, 2020)
The objective was to evaluate alternatives for the control of weeds in the radish culture by measuring their agronomic characteristics in semi-arid conditions. The experiment was carried out in a completely randomized design, with eight treatments corresponding to the forms of weed control, namely: plastic film with color white; a plastic film with color black; donkey grass, Cynodon dactylon; neem leaves, Azadirachta indica A. Juss; donkey grass - incorporated into the soil; neem – incorporated into the soil; solarization and witness. The largest occurrences of weeds were of the species Capim navalha (Hypolytrum pungens), ryegrass (Lolium perene), Bredo fino (Trianthema portulacastrum L.) and Amaranthus spp. The treatments Capim-de-burro embodied (CBE) and soil incorporated neem (SIN) were the most efficient in the control of weeds and also provided greater masses of the aerial part and root of the radish.